Aneurysmal Subarachnoid Hemorrhage: Strategies for Preventing Vasospasm in the Intensive Care Unit - Diringer, Michael N.; Zazulia, Allyson R. (Seminars in Respiratory and Critical Care Medicine, 2017)
This article addresses the intensive care unit (ICU) management of patients with aneurysmal subarachnoid hemorrhage (SAH), with an emphasis on the prevention of cerebral vasospasm and delayed cerebral ischemia (DCI), which are major contributors to morbidity and mortality. Interventions addressing various steps in the development of vasospasm have been attempted, with variable success. Enteral nimodipine remains the only approved measure to potentially prevent DCI. Since oral and intravenous administrations are limited by hypotension, direct administration via sustained-release pellets and intraventricular administration of sustained-release microparticles are being investigated. Studies of other calcium channel blockers have been disappointing. Efforts to remove blood from the subarachnoid space via cisternal irrigation, cisternal or ventricular thrombolysis, and lumbar cerebrospinal fluid drainage have met with limited and variable success, and they remain an area of active investigation. Several interventions that had early promise have failed to show benefit when studied in large trials; these include tirilazad, magnesium, statins, clazosentan, transluminal angioplasty, and hypervolemia.
Keywords: subarachnoid hemorrhage; aneurysm; vasospasm; hypertension; treatment